Asas Keadilan dalam Eksekusi Jaminan Kebendaan Kreditor Separatis pada Kasus Kepailitan terhadap Batasan Waktu Eksekusi - Salsabil Qodrunnada; Elisatris Gultom; Sudaryat Sudaryat (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
A separatist creditor are those holding proprietary security rights over a debtor’s assets, granting them preferential claims in the satisfaction of debts through the execution of the collateral. Article 59 of the Indonesian Bankruptcy and Suspension of Debt Payment Obligations Law (UU KPKPU) restricts the exercise of such execution rights to a period of two months following the declaration of bankruptcy. This limitation raises issues of fairness, as it treats all creditors equally without regard to the legal priority attached to secured creditors. The provision risks undermining the absolute nature of proprietary security rights and deviates from the principle of proportional justice as articulated by Aristoteles. This article adopts a normative legal approach, examining statutory provisions, legal principles, and relevant doctrinal opinions. The findings suggest that the uniform treatment of secured and unsecured creditors after the expiry of the execution period is inconsistent with the fundamental characteristics of secured rights, namely their priority and enforceability against third parties. Accordingly, a revision of the existing legal framework is necessary to ensure the proper and equitable enforcement of secured creditors' rights in bankruptcy proceedings.